A spherical cobalt hydroxide, a preparation method and application thereof
Patent Information
- Application Number
- CN202611457614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本申请提供了一种氢氧化钴及其制备方法及应用,以解决现有氢氧化钴生产工艺不能连续、稳定生产粒径尺寸均一的球形氢氧化钴,并有效解决氢氧化钴易氧化的问题
1.本申请提供一种球形氢氧化钴的制备方法,包括二价钴盐、碱、抗氧化剂溶液在第一管式反应器进行反应,然后在第二管式反应器进行晶型转化,再进行研磨和喷雾干燥得到球形氢氧化钴。其中,第二管式反应器内设置有若干组混合单元片,每组混合单元片包括沿轴向相邻布置的一个左旋片和一个右旋片,所述左旋片和右旋片的旋转角度为90-120°,相邻两组混合单元片的间距为100-150mm。具有该结构设计的第二管式反应器可以有效防止氢氧化钴晶型转化过程中发生团聚,避免氢氧化钴颗粒粒径分布不均;从第二管式反应器出料的球形氢氧化钴粒径分布均匀,再经过后续的研磨处理、喷雾干燥后,制备的球形氢氧化钴颗粒粒径适中,尺寸更加均一。
Smart Images

Figure CN123002906A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of cobalt hydroxide preparation technology, specifically to a spherical cobalt hydroxide, its preparation method, and its application. Background Technology
[0002] Cobalt hydroxide is a key raw material for preparing precursors of lithium-ion battery cathode materials such as lithium cobalt oxide and cobalt tetroxide. Its physicochemical properties, such as particle size distribution, morphology (sphericity), tap density, flowability, and purity, directly determine the electrochemical performance of the lithium-ion cathode materials prepared from it.
[0003] Currently, the industrial production of cobalt hydroxide mostly employs a batch reactor process. This batch reactor process has the following inherent drawbacks: (1) Low production efficiency: There are auxiliary processes such as feeding, discharging and cleaning between each production batch, and the proportion of non-reaction time is relatively high, resulting in low utilization of production equipment and limited overall capacity.
[0004] (2) Poor product consistency: Because the reaction parameters are difficult to keep completely consistent between different production batches, the fluctuation of the reaction parameters leads to batch differences in particle size, morphology and performance of the products, which is not conducive to the consistency of the performance of battery products prepared by them.
[0005] (3) Oxidation problems are prominent: divalent cobalt ions (Co 2+ In alkaline aqueous solutions, it is readily oxidized by oxygen in the air to trivalent cobalt (Co). 3+ This process generates impurities such as high-cobalt hydroxide (Co(OH)3), leading to abnormal product color (changing from pink to brownish-red), a decrease in cobalt hydroxide (Co(OH)2) content, and severely affecting its electrochemical activity in battery materials. Traditional batch processes typically add antioxidants such as sodium sulfite and ascorbic acid at the end of the reaction or after the reaction to prevent Co(OH)2 from oxidizing to Co(OH)3, but the anti-oxidation effect is limited, especially since oxidation easily occurs during post-processing (such as discharging, filtration, washing, and drying).
[0006] (4) Difficulty in morphology control: The growth environment of cobalt hydroxide crystals changes constantly in the intermittent reaction, making it difficult to accurately control the nucleation and growth process of cobalt hydroxide. Therefore, it is difficult to obtain cobalt hydroxide particles with high sphericity and uniform particle size distribution.
[0007] Therefore, there is a need to develop a process that can continuously and stably produce high-quality spherical cobalt hydroxide and effectively solve its oxidation problem. This process has significant industrial application value. Summary of the Invention
[0008] This application provides a cobalt hydroxide, its preparation method, and its application, to solve the problem that existing cobalt hydroxide production processes cannot continuously and stably produce spherical cobalt hydroxide with uniform particle size, and to effectively solve the problem of easy oxidation of cobalt hydroxide.
[0009] In a first aspect, this application provides a method for preparing spherical cobalt hydroxide, comprising the following steps: S1, a divalent cobalt salt solution, an alkaline solution, and an antioxidant solution are fed into the first tubular reactor to react and obtain the first slurry; S2, the first slurry prepared in S1 is fed into the second tubular reactor for crystal transformation to obtain the second slurry; S3, grind the second slurry obtained in S2 to obtain the third slurry; S4, the third slurry prepared in S3 is spray-dried to obtain spherical cobalt hydroxide; In S2, the second tubular reactor is provided with several sets of mixing unit plates. Each set of mixing unit plates includes a left-handed plate and a right-handed plate arranged adjacent to each other along the axial direction. The rotation angle of the left-handed plate and the right-handed plate is 90-120°, and the distance between two adjacent sets of mixing unit plates is 100-150mm.
[0010] In one optional embodiment, the first tubular reactor in S1 is provided with several sets of mixing unit plates. Each set of mixing unit plates includes a left-handed plate and a right-handed plate arranged adjacent to each other along the axial direction. The rotation angle of the left-handed plate and the right-handed plate is 30-50°, and the distance between two adjacent sets of mixing unit plates is 50-80mm.
[0011] Specifically, the number of mixing unit plates set in the first tubular reactor and the second tubular reactor can be calculated based on the flow rate and residence time of the reactants in the first tubular reactor and the second tubular reactor, combined with the rotation angle of each group of mixing unit plates set in the first tubular reactor and the spacing between two adjacent groups of mixing unit plates.
[0012] In one optional embodiment, the particle size Dv50 of the third slurry in S3 is 1.0-1.5 μm.
[0013] In an optional embodiment, the spray drying in S4 employs two-fluid spray drying; Optionally, the gas source for the two-fluid spray drying includes at least one of nitrogen and air, and the gas source pressure is 4-7 barG; as an example, the gas source pressure is 4 barG, 5 barG, 6 barG, 7 barG, or within any range of the above values. Optionally, the gas source temperature for the two-fluid spray drying is 150-300°C; as an example, the gas source temperature for the two-fluid spray drying is 150°C, 200°C, 250°C, 300°C, or within any range of the above values. Optionally, the outlet temperature of the two-fluid spray dryer is 120-160°C; as an example, the outlet temperature of the two-fluid spray dryer is 120°C, 140°C, 150°C, 160°C, or within any range of the above values. Optionally, the mass ratio of the air source to the third slurry in the two-fluid spray drying is (2-6):1; as an example, the mass ratio of the air source to the third slurry in the two-fluid spray drying is 2:1, 3:1, 4:1, 5:1, 6:1, or within any of the above values.
[0014] In one optional embodiment, the reaction temperature in S1 is 20-80°C, and the reaction residence time is 0.1-0.8h; as an example, the reaction temperature in S1 is 20°C, 40°C, 60°C, 80°C, or within any range of the above values; the reaction residence time is 0.1h, 0.2h, 0.4h, 0.6h, 0.8h, or within any range of the above values. And / or, the reaction pressure in S1 is 0-10 barG; as an example, the reaction pressure in S1 is 0 barG, 2 barG, 4 barG, 6 barG, 8 barG, 10 barG, or within any range of the above values; And / or, the pH of the reactants in S1 is controlled to be 9.0-12.0; as an example, the pH of the reactants in S1 is controlled to be 9, 10, 11, 12, or within any range of the above values; And / or, the flow rate of the material in the first tubular reactor in S1 is 0.1-0.6 m / s, optionally 0.1-0.35 m / s; as an example, the flow rate of the material in the first tubular reactor in S1 is 0.1 m / s, 0.2 m / s, 0.3 m / s, 0.35 m / s, 0.4 m / s, 0.5 m / s, 0.6 m / s, or within any range of the above values.
[0015] In one optional embodiment, in step S2, the temperature of the first slurry in the second tubular reactor is controlled to be 20-80°C, and the residence time is 0.2-0.6h, optionally 0.2-0.4h; as an example, in step S2, the temperature of the first slurry in the second tubular reactor is controlled to be 20°C, 40°C, 60°C, 80°C, or within any range of the above values; and the residence time is 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, or within any range of the above values. And / or, the reaction pressure for the crystal form transformation in S2 is 0-10 barG; as an example, the reaction pressure for the crystal form transformation in S2 is 0 barG, 2 barG, 4 barG, 6 barG, 8 barG, 10 barG, or within any of the above values. And / or, the flow rate of the material in the second tubular reactor in S2 is 0.05-0.3 m / s, optionally 0.05-0.2 m / s; as an example, the flow rate of the material in the second tubular reactor in S2 is 0.05 m / s, 0.1 m / s, 0.2 m / s, 0.3 m / s, or within any range of the above values.
[0016] In one optional embodiment, the molar ratio of divalent cobalt salt to alkali in S1 is 1:(2-2.3); as an example, the molar ratio of divalent cobalt salt to alkali in S1 is 1:2, 1:2.1, 1:2.2, 1:2.3, or within any range of the above values; And / or, the molar ratio of divalent cobalt salt to antioxidant in S1 is 1:(0.002-0.01); as an example, the molar ratio of divalent cobalt salt to antioxidant in S1 is 1:0.002, 1:0.004, 1:0.006, 1:0.008, 1:0.01, or within any range of the above values; And / or, the divalent cobalt salt in S1 includes at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride; And / or, the alkaline solution in S1 includes at least one of ammonia, sodium hydroxide solution, and potassium hydroxide solution; And / or, the antioxidant in S1 includes at least one of ascorbic acid, sodium sulfite, hydrazine hydrate, hydroxylamine hydrochloride, and sodium ascorbate.
[0017] In one optional embodiment, the mass concentration of cobalt in the divalent cobalt salt solution in S1 is 90-150 g / L; as an example, the mass concentration of cobalt in the divalent cobalt salt solution in S1 is 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, or within any range of the above values; And / or, the mass concentration of alkali in the alkaline solution described in S1 is 25%-50%; as an example, the mass concentration of alkali in the alkaline solution described in S1 is 25%, 30%, 40%, 50%, or within any range of the above values; And / or, the antioxidant concentration in the antioxidant solution in S1 is 10-50 wt%; as an example, the antioxidant concentration in the antioxidant solution in S1 is 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, or within any range of the above values; And / or, the reaction described in S1 is carried out under nitrogen or an inert atmosphere.
[0018] Specifically, the divalent cobalt salt solution mentioned in S1 refers to an aqueous solution of divalent cobalt salt, the alkaline solution mentioned in S1 refers to an aqueous solution of alkali, and the antioxidant solution mentioned in S1 refers to an aqueous solution of antioxidant.
[0019] Specifically, this application provides a process for continuous production of spherical cobalt hydroxide, comprising the following steps: Step 1: Continuous preparation and metered feeding: Prepare stable concentrations of divalent cobalt salt solution, alkaline solution, and antioxidant solution separately. The mass concentration of cobalt in the divalent cobalt salt solution is 90-150 g / L, the mass concentration of alkali in the alkaline solution is 25%-50%, and the mass concentration of antioxidant in the antioxidant solution is 10-50 wt%. After filtering, the divalent cobalt salt solution, alkaline solution, and antioxidant solution are continuously and stably fed into the first tubular reactor using metering pumps. The first tubular reactor has three inlets to ensure that the divalent cobalt salt solution, alkaline solution, and antioxidant solution are fed simultaneously.
[0020] Step 2: Continuous Reaction and Crystal Transformation: Divalent cobalt salt solution and alkaline solution are continuously fed into the first tubular reactor and undergo a co-precipitation reaction to generate α-type cobalt hydroxide slurry. Simultaneously, a certain amount of antioxidant is added to increase the stability of the α-type cobalt hydroxide slurry. The prepared α-type cobalt hydroxide slurry is continuously fed from the first tubular reactor into the second tubular reactor for cobalt hydroxide crystal transformation (α-type cobalt hydroxide is converted to β-type cobalt hydroxide). The first tubular reactor serves as the reaction device for cobalt hydroxide. Multiple sets of mixing unit plates are installed within this reactor. Each set of mixing unit plates includes one left-handed plate and one right-handed plate arranged adjacent to each other along the axial direction. The rotation angle α between the left-handed and right-handed plates is 30-50°, and the distance between each set of mixing unit plates is 50-80 mm. This structural design is intended to increase the uniformity of the co-precipitation reaction. The reaction conditions in the first tubular reactor are controlled as follows: reaction temperature 20-80℃, pH 9.0-12.0, reaction pressure 0-10 barG, and residence time 0.1-0.8 h. The flow velocity of the cobalt hydroxide slurry in the first tubular reactor is between 0.1-0.6 m / s. The second tubular reactor serves as the cobalt hydroxide crystal transformation device. This reactor also contains multiple sets of mixing unit plates. Each set of mixing unit plates includes one left-handed plate and one right-handed plate arranged adjacent to each other along the axial direction. The rotation angle between the left-handed and right-handed plates is 90-120°, and the distance between each set of mixing unit plates is 100-150 mm. This structural design is used to prevent particle agglomeration during the cobalt hydroxide crystal transformation process, which would lead to uneven particle size distribution. The crystal transformation conditions in the second tubular reactor are controlled as follows: reaction temperature 20-80℃, reaction pressure 0-10 barG, and residence time 0.2-0.6 h. The flow velocity of the material in the second tubular reactor is between 0.05-0.3 m / s.
[0021] Step 3: Continuous Grinding and Particle Size Control: The β-type cobalt hydroxide slurry discharged from the second tubular reactor is continuously fed into an online sand mill for continuous wet grinding. The grinding balls can be made of zirconium oxide, with a filling rate of approximately 20-30%, and the β-type cobalt hydroxide slurry has a filling rate of 50-70%. By adjusting the type, size, and filling rate of the grinding media, the particle size (Dv50) of the β-type cobalt hydroxide particles is controlled within the range of 1.0-1.5 μm, and hard agglomerates are broken up, resulting in a fine β-type cobalt hydroxide slurry with uniform particle size distribution and good stability.
[0022] Step 4: Continuous Drying and Granulation: The ground β-type cobalt hydroxide fine particle slurry is pumped into a two-fluid spray drying tower. During the spray drying process, the atomized droplets are rapidly dried in the high-temperature airflow, the moisture evaporates, and the cobalt hydroxide particles form spherical shapes due to surface tension. By precisely controlling the two-fluid air source temperature (150-300℃), outlet temperature (120-160℃), two-fluid air source pressure (4-7 barG) and air volume, as well as the feed mass ratio of the two-fluid air source and the ground β-type cobalt hydroxide fine particle slurry ((2-6):1), spherical cobalt hydroxide powder with strong antioxidant properties, moderate particle size, high sphericity, good flowability, and low water content (<2%) is finally obtained.
[0023] The spherical cobalt hydroxide powder prepared by the method described in this application has a medium particle size, and medium-sized cobalt hydroxide (Dv50 between 10-20 μm) exhibits more ideal characteristics in terms of process adaptability, storage reliability, and electrochemical performance of the final product. This is because, compared with large-particle-size cobalt hydroxide (Dv50 greater than 20-80 μm), medium-particle-size cobalt hydroxide undergoes more complete mixing and sintering reactions; its acid dissolution rate is moderate, which helps maintain the stability of the precursor co-precipitation system; during electrode preparation, the medium-particle-size range exhibits better compaction density and electrode processability, and the impurities it contains are more easily removed by the water washing process. Compared to ultrafine cobalt hydroxide powder (Dv50 less than 1-10μm), medium-sized cobalt hydroxide has better flowability and is less prone to sticking to the wall or dust during feeding and closed conveying. Compared to ultrafine cobalt hydroxide, medium-sized cobalt hydroxide has a smaller specific surface area, lower moisture content, and higher storage stability, which can effectively delay the oxidation and deterioration process. At the same time, the size shrinkage behavior during sintering is more controllable, which is beneficial to suppressing structural defects such as microcracks in cathode materials during sintering.
[0024] Secondly, this application also provides a spherical cobalt hydroxide prepared according to the above preparation method, wherein the spherical cobalt hydroxide has a sphericity greater than or equal to 0.9, a particle size Dv50 of 10-20 μm, and an SPAN value less than or equal to 0.8.
[0025] Thirdly, this application also provides the application of spherical cobalt hydroxide prepared by the above preparation method or the above-mentioned spherical cobalt hydroxide in the preparation of lithium-ion battery cathode materials.
[0026] The technical solution of this application has the following advantages: 1. This application provides a method for preparing spherical cobalt hydroxide, comprising reacting divalent cobalt salt, alkali, and an antioxidant solution in a first tubular reactor, followed by crystal transformation in a second tubular reactor, and then grinding and spray drying to obtain spherical cobalt hydroxide. The second tubular reactor contains several sets of mixing unit plates, each set including one left-handed and one right-handed plate arranged axially adjacent to each other, with a rotation angle of 90-120° between the left-handed and right-handed plates, and a spacing of 100-150 mm between adjacent sets of mixing unit plates. This structural design of the second tubular reactor effectively prevents agglomeration during the cobalt hydroxide crystal transformation process, avoiding uneven particle size distribution. The spherical cobalt hydroxide particles exiting the second tubular reactor have a uniform particle size distribution, and after subsequent grinding and spray drying, the prepared spherical cobalt hydroxide particles have a moderate particle size and are more uniform in size.
[0027] 2. This application provides a method for preparing spherical cobalt hydroxide, wherein the precipitation reaction of cobalt hydroxide is carried out in a first tubular reactor. The first tubular reactor contains several sets of mixing unit plates. Each set of mixing unit plates includes a left-handed plate and a right-handed plate arranged adjacent to each other along the axial direction. The rotation angle between the left-handed and right-handed plates is 30-50°, and the spacing between adjacent sets of mixing unit plates is 50-80 mm. This first tubular reactor with this specific structural design, as a reaction device for cobalt hydroxide, can increase the uniformity of the reaction. By controlling the rotation angle and spacing of the mixing unit plates, the stability of the reaction system can be maintained.
[0028] 3. This application provides a method for preparing spherical cobalt hydroxide. During the grinding process, the particle size Dv50 of the ground cobalt hydroxide particles is controlled within the range of 1.0-1.5 μm. On the one hand, this can effectively suppress secondary agglomeration during the subsequent spray drying process, and on the other hand, it can make the particle size of the spherical cobalt hydroxide particles prepared after spray drying more uniform.
[0029] 4. This application provides a method for preparing spherical cobalt hydroxide, wherein the spray drying adopts a two-fluid spray drying form, using nitrogen as the two-fluid gas source, and controlling parameters such as the pressure of the two-fluid gas source, the mass ratio of the two-fluid gas source to the slurry, the inlet temperature, and the outlet temperature, so that the final prepared spherical cobalt hydroxide particles have a moderate particle size and meet the product size requirements.
[0030] 5. This application provides a method for preparing spherical cobalt hydroxide, using a first tubular reactor for the precipitation reaction of cobalt hydroxide, with divalent cobalt salt solution, alkaline solution, and antioxidant solution fed simultaneously. This application achieves continuous addition of antioxidants, thus controlling the activity of Co throughout the entire process from the reaction source to product output. 2+Antioxidant protection completely solves the problem of oxidation and deterioration in the traditional batch process of cobalt hydroxide preparation. The product has high main content and pure color (pink).
[0031] 6. This application provides a method for preparing spherical cobalt hydroxide. This application adopts a continuous production process, which can effectively overcome the problem that the growth environment of cobalt hydroxide crystals is constantly changing in the intermittent production process, making it difficult to accurately control the crystal nucleation and growth process. It solves the problem that the particle size, morphology and performance of products vary between different production batches due to fluctuations in reaction conditions. It can continuously, stably and efficiently produce cobalt hydroxide particles with high sphericity, moderate particle size and uniform particle size distribution. At the same time, the prepared cobalt hydroxide particles have good flowability and high Co content (calculated as metal). Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0033] Figure 1 This is a process flow diagram of the preparation of spherical cobalt hydroxide according to Example 1 of this application; Figure 2 This is a partially enlarged view of the first tubular reactor used in the preparation process of spherical cobalt hydroxide in Example 1 of this application.
[0034] Explanation of reference numerals in the attached figures: 1. Alkali inlet; 2. Cobalt salt solution inlet; 3. Antioxidant solution inlet; 4. First tubular reactor; 5. Nitrogen inlet; 6. Sand mill; 7. Second tubular reactor; 8. Exhaust port; 9. Two-fluid spray drying tower; 10. Mixing unit plate; α, rotation angle of left-handed and right-handed plates in each mixing unit plate group; h, spacing between two adjacent mixing unit plate groups. Detailed Implementation
[0035] The following embodiments are provided to better understand this application. However, the following embodiments do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining the features of this application with other prior art, falls within the scope of protection of this application.
[0036] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0037] The test methods for the performance parameters of the cobalt hydroxide products prepared in the various embodiments and comparative examples of this application are as follows: Test method for wet content of cobalt hydroxide: The test is performed using a halogen moisture analyzer (the basic principle is to calculate the weight loss ratio during drying). The prepared cobalt hydroxide sample is dried at 150-180℃ until the mass of the cobalt hydroxide sample remains stable. The wet content is calculated using the following formula:
[0038] The values represent the moisture content, m1 represents the sample mass before drying, and m2 represents the sample mass after drying. Cobalt hydroxide sphericity test method: The sphericity test of cobalt hydroxide is carried out by dynamic image analysis (DIA). The cobalt hydroxide particles are dispersed by compressed air and sprayed through the measurement window. When the particles pass through the measurement window, a high-speed camera captures dynamic images of the particles flying at a frequency of hundreds of frames per second. Then, the sphericity of the particles is calculated by analyzing the images through software.
[0039] Test method for cobalt hydroxide particle size: Laser diffraction method is used, based on Mie scattering theory, to measure the scattered light intensity distribution and invert the particle size Dv10, Dv50, and Dv90. Test method for SPAN value of cobalt hydroxide: The SPAN value is calculated using the following formula based on the cobalt hydroxide particle size parameters Dv10, Dv50, and Dv90: .
[0040] Test method for bulk density of cobalt hydroxide: The cobalt hydroxide sample flows freely through a standard funnel into a graduated cylinder with a volume of 25 cm³. After the sample surface is leveled, it is weighed, and the density is calculated. The standard funnel is a standard Hall effect flowmeter funnel, made of stainless steel or glass, with a cone angle of 60°, an inlet diameter of 80 mm, and an outlet diameter of 2.5 mm or 5.0 mm, depending on the flowability of the cobalt hydroxide sample. If clogging occurs when using a standard Hall effect flowmeter funnel with an outlet diameter of 2.5 mm, then a standard Hall effect flowmeter funnel with an outlet diameter of 5.0 mm should be used.
[0041] Test method for the angle of repose of cobalt hydroxide: Fix the funnel at a specific high point above the horizontal plate, so that the height of the funnel outlet from the surface of the horizontal plate is 60mm. After adding 50g of cobalt hydroxide sample, open the bottom outlet of the funnel to allow the cobalt hydroxide sample to accumulate freely into a cone. Measure the angle between the cone height and the base radius to obtain the angle of repose.
[0042] Test method for Co content in cobalt hydroxide: Atomic absorption spectrometry is used. After dissolving the cobalt hydroxide sample, the absorbance is measured at a wavelength of 240.7 nm.
[0043] Example 1 This embodiment provides a method for preparing spherical cobalt hydroxide. The process flow diagram for preparing spherical cobalt hydroxide is shown below. Figure 1 As shown, the parameters of each component and the preparation method steps are as follows: S1. Prepare a cobalt sulfate aqueous solution with a cobalt element concentration of 110 g / L, an ammonia aqueous solution with a mass fraction of 30%, and an ascorbic acid (VC) aqueous solution with a mass fraction of 10%. All three solutions are filtered through a filter cartridge with a pore size of 0.5 μm. S2, the filtered solutions described above are continuously pumped into the first tubular reactor 4 via a precision metering pump at a molar ratio of cobalt sulfate: ammonia: vitamin C of 1:2.05:0.005. The ammonia solution is fed through the alkali inlet 1, the cobalt sulfate solution through the cobalt salt solution inlet 2, and the ascorbic acid (vitamin C) solution through the antioxidant solution inlet 3. The reaction is carried out under a nitrogen atmosphere, with the reaction temperature controlled at 60±1℃. The overall pressure inside the first tubular reactor 4 is maintained at 3-5 barG. A small amount of alkali solution (30% ammonia solution by mass) is automatically added dropwise to maintain the pH of the material system at 11.0±0.1. The residence time of the material system in the first tubular reactor 4 is 0.28 hours, and the flow rate inside the first tubular reactor 4 is 0.2 m / s. The first tubular reactor 4 is equipped with several sets of mixing unit plates 10. The rotation angle α of the left-handed and right-handed plates in each set of mixing unit plates is 45°, and the distance h between two adjacent sets of mixing unit plates is 60mm. The material discharged from the first tubular reactor 4 enters the second tubular reactor 7, where the cobalt hydroxide crystal form conversion takes place. The crystal form conversion temperature is controlled at 60±1℃. The overall pressure in the second tubular reactor 7 is maintained at 1-3 barG. The residence time of the material in the second tubular reactor 7 is 0.38 hours, and the flow rate in the second tubular reactor 7 is 0.11m / s. The second tubular reactor 7 is equipped with several sets of mixing unit plates. The rotation angle of the left-handed and right-handed plates in each set of mixing unit plates is 95°, and the distance h between two adjacent sets of mixing unit plates is 140mm.
[0044] S3, the material discharged from the second tubular reactor 7 is directly pumped into the sand mill 6, which uses zirconia beads as grinding media. The grinding media filler is 25% and the material filler is 65%. The material is continuously ground at a speed of 2500 rpm. After the material passes through the sand mill continuously in one go, a uniform slurry with a Dv50 of about 1.2μm is obtained.
[0045] S4. The ground slurry is fed into a two-fluid spray drying tower 9. Nitrogen is used as the two-fluid gas source, entering through nitrogen inlet 5. The inlet temperature is set to 200℃, and the outlet temperature is controlled at 120℃. The exhaust gas is discharged through exhaust port 8. The gas source pressure is 7 barG, and the mass ratio of the gas source inlet volume to the slurry feed volume is 3:1. Light pink cobalt hydroxide powder with high sphericity is obtained.
[0046] Test results: The cobalt hydroxide product has a wet content of 1.8%, a sphericity of 0.93, a Dv50 of 11μm, a SPAN value of 0.50, a bulk density of 0.60g / cm³, an angle of repose of 31°, and a Co content (calculated as metal) of 61.6%. The cobalt hydroxide sample showed no significant color change after being left exposed to air for 48 hours.
[0047] Example 2 This embodiment provides a method for preparing spherical cobalt hydroxide. The component parameters and preparation steps are as follows: S1. Prepare a cobalt sulfate aqueous solution with a cobalt element concentration of 130 g / L, an ammonia aqueous solution with a mass fraction of 40%, and a sodium sulfite aqueous solution with a mass fraction of 10%. All three solutions are filtered through a filter cartridge with a pore size of 0.5 μm. S2, the filtered solutions described above are continuously pumped into the first tubular reactor via a precision metering pump at a molar ratio of cobalt sulfate: ammonia: sodium sulfite of 1:2.1:0.004. The reaction is carried out under a nitrogen atmosphere, with the reaction temperature controlled at 30±1℃ and the overall pressure in the first tubular reactor maintained at 8-10 barG. The pH of the system is maintained at 12.0±0.1 by automatically adding a small amount of alkali solution (40% ammonia solution by mass). The average residence time of the material system in the first tubular reactor is 0.44 hours, and the flow rate in the first tubular reactor is 0.31 m / s. The first tubular reactor is equipped with several sets of mixing unit plates, with the rotation angle of the left-handed and right-handed plates in each set of mixing unit plates being 50°, and the spacing between two adjacent sets of mixing unit plates being 70 mm. The material exiting the first tubular reactor enters the second tubular reactor, where the crystal transformation temperature is controlled at 30±1℃, and the overall pressure in the second tubular reactor is maintained at 5-8 barG. The residence time of the material in the second tubular reactor is 0.24 hours, the flow velocity in the second tubular reactor is 0.18 m / s, and the second tubular reactor is equipped with several sets of mixing unit plates. The rotation angle of the left-handed and right-handed plates in each set of mixing unit plates is 110°, and the distance between two adjacent sets of mixing unit plates is 110 mm.
[0048] S3, the material discharged from the second stage reactor is directly pumped into a sand mill with zirconia beads as the grinding media. The grinding media has a filler content of 24% and the material has a filler content of 62%. The material is continuously ground at a speed of 2800 rpm. After the material passes through the sand mill continuously in one go, a uniform slurry with a Dv50 of about 1.0 μm is obtained.
[0049] S4. The ground slurry is fed into a two-fluid spray drying tower, using nitrogen as the two-fluid gas source. The inlet temperature is set to 250℃, the outlet temperature is controlled at 130℃, the gas source pressure is 5 barG, and the mass ratio of the gas source inlet volume to the slurry feed volume is 4:1. Light pink cobalt hydroxide powder with high sphericity is obtained.
[0050] Test results: The cobalt hydroxide product has a wet content of 1.6%, a sphericity of 0.92, a Dv50 of 15μm, a SPAN value of 0.60, a bulk density of 0.70g / cm³, an angle of repose of 30°, and a Co content (calculated as metal) of 61.6%. The cobalt hydroxide sample showed no significant color change after being left exposed to air for 48 hours.
[0051] Example 3 This embodiment provides a method for preparing spherical cobalt hydroxide. The component parameters and preparation steps are as follows: S1. Prepare a cobalt nitrate aqueous solution with a cobalt element concentration of 90 g / L, a sodium hydroxide solution with a mass fraction of 25%, and an ascorbic acid (VC) aqueous solution with a mass fraction of 10%. All three solutions are filtered through a filter cartridge with a pore size of 0.5 μm. S2, the filtered solutions described above are continuously pumped into the first tubular reactor via a precision metering pump at a molar ratio of cobalt nitrate: sodium hydroxide: vitamin C of 1:2.0:0.002. The reaction takes place under a nitrogen atmosphere, with the reaction temperature controlled at 60±1℃. The overall pressure within the first tubular reactor is maintained at 3-5 barG. A small amount of alkali solution (25% sodium hydroxide solution by mass) is automatically added dropwise to maintain the pH of the material system at 9.0. The residence time of the material system in the first tubular reactor is 0.78 hours, and the flow rate is 0.18 m / s. The first tubular reactor is equipped with several sets of mixing unit plates, each with a 50° rotation angle between the left-handed and right-handed plates, and a 50mm spacing between adjacent sets of mixing unit plates. The material exiting the first tubular reactor enters the second tubular reactor, where the cobalt hydroxide crystal form transformation occurs. The crystal form transformation temperature is controlled at 60±1℃, and the overall pressure within the second tubular reactor is maintained at 1-3 barG. The residence time of the material in the second tubular reactor is 0.28 hours, the flow velocity in the second tubular reactor is 0.08 m / s, and the second tubular reactor is equipped with several sets of mixing unit plates. The rotation angle of the left-handed and right-handed plates in each set of mixing unit plates is 120°, and the spacing between two adjacent sets of mixing unit plates is 100 mm.
[0052] S3, the material discharged from the second stage reactor is directly pumped into a sand mill with zirconia beads as the grinding media. The grinding media filler is 20% and the material filler is 70%. The material is continuously ground at a speed of 2550 rpm. After the material passes through the sand mill continuously in one go, a uniform slurry with a Dv50 of about 1.5 μm is obtained.
[0053] S4. The ground slurry is fed into a two-fluid spray drying tower, using nitrogen as the two-fluid gas source. The inlet temperature is set to 150℃, the outlet temperature is controlled at 120℃, the gas source pressure is 7 barG, and the mass ratio of the gas source inlet volume to the slurry feed volume is 2:1. Light pink cobalt hydroxide powder with high sphericity is obtained.
[0054] Test results: The cobalt hydroxide product has a wet content of 1.5%, a sphericity of 0.92, a Dv50 of 12μm, a SPAN value of 0.58, a bulk density of 0.61g / cm³, an angle of repose of 31°, and a Co content (calculated as metal) of 61.6%. The cobalt hydroxide sample showed no significant color change after being left exposed to air for 48 hours.
[0055] Example 4 This embodiment provides a method for preparing spherical cobalt hydroxide. The component parameters and preparation steps are as follows: S1. Prepare a cobalt sulfate aqueous solution with a cobalt element concentration of 150 g / L, an ammonia aqueous solution with a mass fraction of 50%, and an ascorbic acid (VC) aqueous solution with a mass fraction of 50%. All three solutions are filtered through a filter cartridge with a pore size of 0.5 μm.
[0056] S2, the filtered solutions described above are continuously pumped into the first tubular reactor via a precision metering pump at a molar ratio of cobalt sulfate: ammonia: vitamin C of 1:2.3:0.01. The reaction temperature is controlled at 60±1℃, and the pressure inside the first tubular reactor is maintained at 3-5 barG. The pH of the material system is maintained at 11.0±0.1 by automatically adding a small amount of alkali solution (50% ammonia solution). The residence time of the material system in the first tubular reactor is 0.61 hours, and the flow rate is 0.11 m / s. The first tubular reactor is equipped with several sets of mixing unit plates, with the rotation angle between the left-handed and right-handed plates in each set being 30°, and the spacing between two adjacent sets of mixing unit plates being 80 mm. The material exiting the first tubular reactor enters the second tubular reactor, where the cobalt hydroxide crystal transformation takes place. The crystal transformation temperature is controlled at 60±1℃, and the pressure inside the second tubular reactor is maintained at 1-3 barG. The residence time of the material in the second tubular reactor is 0.28 hours, the flow velocity in the second tubular reactor is 0.08 m / s, and the second tubular reactor is equipped with several sets of mixing unit plates. The rotation angle of the left-handed and right-handed plates in each set of mixing unit plates is 90°, and the spacing between two adjacent sets of mixing unit plates is 150 mm.
[0057] S3, the material discharged from the second stage reactor is directly pumped into a sand mill with zirconia beads as the grinding media. The grinding media filler is 25% and the material filler is 60%. The material is continuously ground at a speed of 2500 rpm. After the material passes through the sand mill continuously in one go, a uniform slurry with a Dv50 of about 1.2 μm is obtained.
[0058] S4. The ground slurry is fed into a two-fluid spray drying tower, using nitrogen as the two-fluid gas source. The inlet temperature is set to 300℃, the outlet temperature is controlled at 160℃, the gas source pressure is 7 barG, and the mass ratio of the gas source inlet volume to the slurry feed volume is 6:1. Light pink cobalt hydroxide powder with high sphericity is obtained.
[0059] Test results: The cobalt hydroxide product has a wet content of 1.4%, a sphericity of 0.94, a Dv50 of 10μm, a SPAN value of 0.54, a bulk density of 0.60g / cm³, an angle of repose of 33°, and a Co content (calculated as metal) of 61.7%. The cobalt hydroxide sample showed no significant color change after being left exposed to air for 48 hours.
[0060] Example 5 This embodiment provides a method for preparing spherical cobalt hydroxide. The component parameters and preparation steps are as follows: S1. Prepare a cobalt sulfate aqueous solution with a cobalt element concentration of 130 g / L, an ammonia aqueous solution with a mass fraction of 40%, and a sodium sulfite aqueous solution with a mass fraction of 30%. All three solutions are filtered through a filter cartridge with a pore size of 0.5 μm. S2, the filtered solutions described above are continuously pumped into the first tubular reactor via a precision metering pump at a molar ratio of cobalt sulfate: ammonia: sodium sulfite of 1:2.1:0.004. The reaction is carried out under a nitrogen atmosphere, with the reaction temperature controlled at 80℃ and the overall pressure in the first tubular reactor maintained at 3-5 barG. The pH of the system is maintained at 11.0±0.1 by automatically adding a small amount of alkali solution (40% ammonia solution by mass). The average residence time of the material system in the first tubular reactor is 0.18 hours, and the flow rate in the first tubular reactor is 0.16 m / s. The first tubular reactor is equipped with several sets of mixing unit plates, with the rotation angle of the left-handed and right-handed plates in each set of mixing unit plates being 45°, and the spacing between two adjacent sets of mixing unit plates being 60 mm. The material exiting the first tubular reactor enters the second tubular reactor, where the crystal transformation temperature is controlled at 80℃, and the overall pressure in the second tubular reactor is maintained at 8-10 barG. The residence time of the material in the second tubular reactor is 0.35 hours, the flow velocity in the second tubular reactor is 0.16 m / s, and the second tubular reactor is equipped with several sets of mixing unit plates. The rotation angle of the left-handed and right-handed plates in each set of mixing unit plates is 110°, and the distance between two adjacent sets of mixing unit plates is 110 mm.
[0061] S3, the material discharged from the second tubular reactor is directly pumped into a sand mill with zirconia beads as the grinding media. The grinding media is 30% filled and the material is 50% filled. The material is continuously ground at a speed of 2800 rpm. After the material passes through the sand mill continuously in one go, a uniform slurry with a Dv50 of about 1.0 μm is obtained.
[0062] S4. The ground slurry is fed into a two-fluid spray drying tower, using nitrogen as the two-fluid gas source. The inlet temperature is set to 250℃, the outlet temperature is controlled at 130℃, the gas source pressure is 5 barG, and the mass ratio of the gas source inlet volume to the slurry feed volume is 4:1. Light pink cobalt hydroxide powder with high sphericity is obtained.
[0063] Test results: The cobalt hydroxide product has a wet content of 1.7%, a sphericity of 0.93, a Dv50 of 13μm, a SPAN value of 0.62, a bulk density of 0.63g / cm³, an angle of repose of 32°, and a Co content (calculated as metal) of 61.6%. The cobalt hydroxide sample showed no significant color change after being left exposed to air for 48 hours.
[0064] Comparative Example 1 This comparative example provides a method for preparing cobalt hydroxide. The difference between this comparative example and Example 2 is that the method for preparing cobalt hydroxide provided in this comparative example uses a conventional stirred tank reactor instead of the tubular reactor in step S2 of Example 2. That is, the method for preparing cobalt hydroxide provided in this comparative example does not involve a tubular reactor. Other component parameters and preparation methods are the same as in Example 2. Step S2 in this comparative example is as follows: Three filtered solutions (cobalt sulfate aqueous solution with a cobalt element mass concentration of 130 g / L, ammonia aqueous solution with a mass fraction of 40%, and sodium sulfite aqueous solution with a mass fraction of 10%) were added to a stirred batch reactor in a Co:OH:VC molar ratio of 1:2.1:0.004. The overall reaction temperature was maintained at 30°C, and the reaction time was 0.5 h. The pH of the material system was maintained at 12.0 by adding a small amount of alkali solution (ammonia aqueous solution with a mass fraction of 40%). After the reaction was completed, the system was allowed to stand for 0.3 h (i.e., the crystal transformation time was 0.3 h), and the system temperature was maintained at 30°C.
[0065] Test results: The cobalt hydroxide product has a normal color and no significant color change after being left open in the air for 48 hours. The material is obviously ellipsoidal with a sphericity of 0.25, poor flowability, an angle of repose of 43°, a Dv50 of 28μm, a SPAN value of around 1.8, and a wide particle size distribution.
[0066] Comparative Example 2 This comparative example provides a method for preparing spherical cobalt hydroxide. The difference between this comparative example and Example 2 is that the method for preparing cobalt hydroxide provided in this comparative example does not involve a sand milling process (i.e., step S3 in Example 2). Other component parameters and preparation methods are the same as in Example 2.
[0067] Test results: The cobalt hydroxide product has a normal color and no significant color change after being left open in the air for 48 hours. The material is clearly ellipsoidal with a sphericity of 0.30, an angle of repose of 42°, a Dv50 of 24μm, a SPAN value of around 1.6, and a wide particle size distribution.
[0068] Comparative Example 3 This comparative example provides a method for preparing spherical cobalt hydroxide. The difference between this comparative example and Example 2 is that the method for preparing cobalt hydroxide provided in this comparative example does not include a second tubular reactor, and the residence time of the reactants in the first tubular reactor is extended to 0.68 hours, so that the crystal form transformation of cobalt hydroxide occurs in the first tubular reactor instead of in the second tubular reactor in Example 2. Other component parameters and preparation methods are the same as in Example 2.
[0069] Test results: The cobalt hydroxide product has a normal color and no significant color change after being left open in the air for 48 hours. The sphericity is 0.90, the Dv50 is 22μm, the SPAN value is 1.0, the bulk density is 0.90g / cm³, and the angle of repose is 36°.
[0070] Comparative Example 4 This comparative example provides a method for preparing spherical cobalt hydroxide. The difference between this comparative example and Example 2 is that the structure of the tubular reactor used in the method for preparing cobalt hydroxide provided in this comparative example is different. In the first tubular reactor, the rotation angle of the left-handed and right-handed plates in each mixing unit is 50°, and the spacing between two adjacent mixing unit plates is 70 mm. The second tubular reactor is a shell-and-tube reactor, and no mixing unit plates are set inside the tubes. Other component parameters and preparation methods are the same as in Example 2.
[0071] Test results: The cobalt hydroxide product has a normal color and no significant color change after being left open in the air for 48 hours. The sphericity is 0.90, the Dv50 is 23μm, the SPAN value is 1.1, the bulk density is 1.02 g / cm³, and the angle of repose is 38°.
[0072] Comparative Example 5 This comparative example provides a method for preparing spherical cobalt hydroxide. The difference between this comparative example and Example 2 is that the first tubular reactor used in the method for preparing cobalt hydroxide provided in this comparative example is the same as that in Example 2. In the second tubular reactor used, the rotation angle of the left-handed and right-handed plates in each group of mixing unit plates is 150° (not within the range of 90-120°), and the distance between two adjacent groups of mixing unit plates is 200mm (not within the range of 100-150mm). Other component parameters and preparation methods are the same as those in Example 2.
[0073] Test results: The cobalt hydroxide product has a normal color and no significant color change after being left open in the air for 48 hours. The sphericity is 0.91, the Dv50 is 25μm, the SPAN value is around 1.5, the bulk density is 0.96g / cm³, and the angle of repose is 37°.
[0074] The test results of the examples and comparative examples show that the cobalt hydroxide prepared in each example has a medium particle size (Dv50 between 10-15 μm), uniform particle size distribution (SPAN value between 0.50-0.62), high sphericity (sphericity greater than or equal to 0.92), good flowability (small angle of repose), and the Co content in the cobalt hydroxide is greater than 61.5%, and it is not easily oxidized.
[0075] Comparative Example 1 uses a traditional batch process to prepare cobalt hydroxide. The cobalt hydroxide particles prepared in Comparative Example 1 are obviously ellipsoidal, with a Dv50 of 28 μm, a SPAN value of about 1.8, a wide particle size distribution, poor flowability, and poor product uniformity.
[0076] In Comparative Example 2, the particle size in the slurry was not controlled by a sand milling process during the preparation of cobalt hydroxide. The particle size of the material discharged from the second tubular reactor was relatively large. During the two-fluid spray drying process, large particles would form "bridging" between each other, resulting in hard agglomerates that were difficult to disperse. The cobalt hydroxide product prepared in Comparative Example 2 was obviously ellipsoidal with a Dv50 greater than 20 μm, a wide particle size distribution, and poor flowability.
[0077] In Comparative Example 3, only the first tubular reactor was used for the cobalt hydroxide precipitation reaction and cobalt hydroxide crystal form conversion. During the cobalt hydroxide crystal form conversion, the viscosity of the material increased. The design parameters of the rotation angle of each mixing unit plate and the spacing between adjacent mixing unit plates in the first tubular reactor could not meet the material dispersion requirements, resulting in some cobalt hydroxide material adhering and agglomerating on the mixing unit plates, thus affecting the product indicators. The cobalt hydroxide product prepared in Comparative Example 3 had a sphericity of 0.90, a Dv50 greater than 20 μm, a bulk density of 0.9 g / cm³, an angle of repose of 36°, and a SPAN value of 1.0.
[0078] In Comparative Example 4, a two-stage tubular reactor was used for the cobalt hydroxide precipitation reaction and crystal transformation. Because the second tubular reactor was a shell-and-tube reactor, there were no mixing units within the tubes, resulting in poor material dispersion. The cobalt hydroxide product prepared in Comparative Example 4 had a sphericity of 0.90, a Dv50 greater than 20 μm, a bulk density of 1.02 g / cm³, an angle of repose of 38°, and a SPAN value of 1.1.
[0079] In Comparative Example 5, a first tubular reactor and a second tubular reactor were used for the cobalt hydroxide precipitation reaction and crystal transformation. Due to the excessive rotation angle of each mixing unit plate and the excessive spacing between adjacent mixing unit plates in the second tubular reactor, the cobalt hydroxide material was poorly dispersed during the crystal transformation process. During the crystal transformation, α-type cobalt hydroxide crystals agglomerated into relatively large particles in the second tubular reactor, which affected the subsequent sand milling and two-fluid drying effects, resulting in larger particle size and SPAN value of the final cobalt hydroxide particles.
[0080] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this application.
Claims
1. A method for preparing spherical cobalt hydroxide, characterized in that, Includes the following steps: S1, a divalent cobalt salt solution, an alkaline solution, and an antioxidant solution are fed into the first tubular reactor to react and obtain the first slurry; S2, the first slurry prepared in S1 is fed into the second tubular reactor for crystal transformation to obtain the second slurry; S3, grind the second slurry obtained in S2 to obtain the third slurry; S4, the third slurry prepared in S3 is spray-dried to obtain spherical cobalt hydroxide; In S2, the second tubular reactor is provided with several sets of mixing unit plates. Each set of mixing unit plates includes a left-handed plate and a right-handed plate arranged adjacent to each other along the axial direction. The rotation angle of the left-handed plate and the right-handed plate is 90-120°, and the distance between two adjacent sets of mixing unit plates is 100-150mm.
2. The preparation method according to claim 1, characterized in that, In S1, the first tubular reactor is provided with several sets of mixing unit plates. Each set of mixing unit plates includes a left-handed plate and a right-handed plate arranged adjacent to each other along the axial direction. The rotation angle of the left-handed plate and the right-handed plate is 30-50°, and the distance between two adjacent sets of mixing unit plates is 50-80mm.
3. The preparation method according to claim 1 or 2, characterized in that, The particle size Dv50 of the third slurry described in S3 is 1.0-1.5 μm.
4. The preparation method according to any one of claims 1-3, characterized in that, The spray drying described in S4 employs two-fluid spray drying; Optionally, the gas source for two-fluid spray drying includes at least one of nitrogen and air, and the gas source pressure is 4-7 barG; Optionally, the gas source temperature for two-fluid spray drying is 150-300℃; Optionally, the outlet temperature of the two-fluid spray dryer is 120-160℃; Optionally, the mass ratio of the air source to the third slurry in the two-fluid spray drying is (2-6):
1.
5. The preparation method according to any one of claims 1-3, characterized in that, The reaction temperature described in S1 is 20-80℃, and the reaction residence time is 0.1-0.8h; And / or, the reaction pressure in S1 is 0-10 barG; And / or, the pH of the reactants in S1 is controlled to be 9.0-12.0; And / or, the flow rate of the material in the first tubular reactor in S1 is 0.1-0.6 m / s, optionally 0.1-0.35 m / s.
6. The preparation method according to any one of claims 1-5, characterized in that, In S2, the temperature of the first slurry in the second tubular reactor is controlled at 20-80℃, and the residence time is 0.2-0.6h, optionally 0.2-0.4h; And / or, the reaction pressure for crystal form transformation in S2 is 0-10 barG; And / or, the flow rate of the material in the second tubular reactor in S2 is 0.05-0.3 m / s, optionally 0.05-0.2 m / s.
7. The preparation method according to claim 1, characterized in that, The molar ratio of divalent cobalt salt to alkali in S1 is 1:(2-2.3). And / or, the molar ratio of divalent cobalt salt to antioxidant in S1 is 1:(0.002-0.01). And / or, the divalent cobalt salt in S1 includes at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride; And / or, the alkaline solution in S1 includes at least one of ammonia, sodium hydroxide solution, and potassium hydroxide solution; And / or, the antioxidant in S1 includes at least one of ascorbic acid, sodium sulfite, hydrazine hydrate, hydroxylamine hydrochloride, and sodium ascorbate.
8. The preparation method according to claim 1, characterized in that, The mass concentration of cobalt in the divalent cobalt salt solution described in S1 is 90-150 g / L; And / or, the mass concentration of alkali in the alkaline solution described in S1 is 25%-50%; And / or, the antioxidant concentration in the antioxidant solution described in S1 is 10-50 wt%; And / or, the reaction described in S1 is carried out under nitrogen or an inert atmosphere.
9. A spherical cobalt hydroxide prepared by the preparation method according to any one of claims 1-8, characterized in that, The spherical cobalt hydroxide has a sphericity greater than or equal to 0.9, a particle size Dv50 of 10-20 μm, and a SPAN value less than or equal to 0.
8.
10. The application of spherical cobalt hydroxide prepared by any one of claims 1-8 or spherical cobalt hydroxide as described in claim 9 in the preparation of cathode materials for lithium-ion batteries.
